Students’ Anxiety In Speaking Performance For Formal Setting Of Tenth Grade At MAS Mathlaul Falah Lempuyang - Nunung Nuraini; Yudi Juniardi (Journal of Linguistics, Literacy, and Pedagogy, 2023)
Anxiety is the one psicological factor that has an important role in affecting language learning outcomes. It is a feeling of disquiet that happened in particular moment of time. Students’ anxiety here means that anxious children often have to exert more effort to perform well because they’re trying to manage their anxiety while executing a task. This research will use qualitative method to know the problems that arise in the event after interview and giving the students qustionnaire guide. The population of this study is students of tenth grade at MA Mathlaul Falah Lempuyang how join at English Class as 30 students. The researcher selected 9 participants for re-confirm the questionnaire guide they had answered. To collect data in this study is more appropriate to use questionnaire method because it allowed students to answer, can get answers appropriate or relevant to the research objectives and facilitated retrieval of data in large quantities. Based on the data finding in this research, the researcher offers suggestion to the student teacher to keep the low Level as the level of anxiety to students’ speaking, because at this level students will be more vigilant in preparation speaking and they will be better prepared to receive the material as well as the evaluation given by the teacher. As the most common factor that fear of negative evaluation of teachers should the students are not too afraid about it, because all will return for the good of the students themselves.